Carbon mineralization potential of non-edible oil-seed cakes at different composting stages in soil - A, VASUDHA UDUPA; SHIVANNA, M B; GOWDA, BALAKRISHNA (The Indian Journal of Agricultural Sciences, 2022)
Non-edible oil-seed cakes of neem, madhuca and simarouba were subjected to natural decomposition by simple pit method in CR design during 2020–21 at UAS, GKVK, Bangalore. The physicochemical parameters temperature, pH, EC, mineral nutrients, lignin contents and phytotoxicity of oil-seed cakes during decomposition were determined at 30 days intervals for 90 days. Simultaneously, samples were also studied for the C-mineralization pattern by measuring CO2-C evolution during 60 days of the aerobic incubation experiment. The first-order kinetic model was used to describe the C-mineralization and calculate potentially mineralizable C. The decomposition of oil-seed cakes led to an increase in mineral nutrients and a decrease in lignin content and toxicity. After 60 days of the addition of soil with oil-seed cakes at different stages of compost, the cumulative C-mineralization occurred in the order neem<madhuca<simarouba. The kinetic model suggested the presence of potentially mineralizable C (C0) in the undecomposed simarouba oil-seed cake than in the neem and madhuca. This C0 decreased at 90 days of composting in all oil-seed cakes. The NMC was high in undecomposed oil-seed cakes in the order S-0>M-0>N-0. The CMC value of mature compost (90 days) was lower in neem and simarouba (6%) than in madhuca oil-seed cakes (22%). The low C-mineralization potential of raw and composted neem oil-seed cake suggested its superiority in the improvement of SOC. However, complete composting of oil-seed cakes of madhuca and simarouba was necessary for C-sequestration.